Hubungan Antara Akses KB dengan Pemilihan Kontrasepsi Hormonal dan Non Hormonal di Kabupaten Purworejo - Sri Panuntun, Siswanto Agus Wilopo, Lina Kurniawati (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: The report of 2002-2003 Indonesia’s Demographic and Health Survey (IDHS) suggests that the prevalence of family planning in Indonesia reach 60 percent with the hormonal contraceptive increase by 16 percent and the non hormonal contraceptive decrease by 7 percent. Generally, the choice of contraceptives is based on clear reasons to regulate the birth spacing or to limit births. Factors determining the choice of non hormonal contraceptives include physical access (distance), economy (cost), administration (service resource) and cognitive accesses (knowledge).Objective: To investigate the relationship between contraceptive accesses and the choice of hormonal and non hormonal contraceptives in Purworejo District.Method: This was an observational study with a case control study design.Subject: Samples were married women 20-35 years of age that became the new acceptors with the choice of non hormonal contraceptives (IUD) as the case (133 women) and of hormonal contraceptives (pill and injectable) as the control (133 women) from 1 January 2004 to 31 December 2004.Data analysis: The qualitative data analyses used were univariable, bivariable and multivariable. Statistical test used chi-square and logistic regression.Results: The bivariable and multivariable analyses showed that there was a relationship between family planning demand and the choice of non hormonal contraceptives. Respondent residing far from family planning services tended to choose non hormonal contraceptives with a chance of 1.9 times higher (OR=9.5;CI95%=1.16-3.19). The variable that had the greatest chance to influence respondents to choose non hormonal contraceptives was cost that was 7.5 times (OR=7.5; CI 95% = 2.60-21.87). The respondents that utilized private facilities tended to choose non hormonal contraceptives.Conclusion: Respondents with family planning demand to limit births were likely to choose non hormonal contraceptives. Other factors affecting the choice of non hormonal contraceptives were income.Keywords: family planning accesses, family planning demand, choice of hormonal and non hormonalcontraceptives, case control